Upacara Adat Posuo (Pingitan) serta Pelaksaannya pada Masyarakat Buton - Fahrian, Rajlun; La Yunus; Fadli; Irfan; Rosita; Suharni (LANCAH: Jurnal Inovasi dan Tren, 2024)
There is no society without culture, and conversely there is no culture without society as a forum and supporter. Society and culture are two things that cannot be separated from each other. The organization of the latter posua generally consists of families who are still in the same kinship ties. In the ceremony, each family entrusts their children as participants. This merger is usually carried out taking into account the capabilities of a family. Families who join in the ceremony also provide financial support (bhaku, bura, te mantomu) or other needs for the ceremony. Other activities refer to traditional ceremonies that do not originate from Islam, but are tolerated and maintained after undergoing a modification process of Islamization from their original form. Traditional rituals in their current form do not endanger Islamic beliefs, in fact they have been classified as manifestations of the beliefs themselves and are used as symbols of Islam typical of certain regions.